The Effect of Efflurage Massage on Sleep Quality in Postpartum Women at Bayu Asih Hospital, Purwakarta Regency - Handayani, Teti Yuli; Oktiawati, Nita (Jurnal Indonesia Sosial Sains, 2025)
The moment of the birth of a child is both the most stressful and exciting time because of the arrival of a baby. However, mothers who have just given birth often suffer from postpartum fatigue, especially in the early days, which results in disrupted sleep. Consequently, these mothers can easily become stressed and may experience postpartum blues or depressive disorders. This study aims to determine The Effect of Efflurage Massage on Sleep Quality in Postpartum Women at Bayu Asih Hospital, Purwakarta Regency in 2024. The research used a one-group pretest and posttest experimental design with a sample of 34 postpartum mothers. The study was conducted from July to August 2024. The dependent variable in this study was sleep quality among breastfeeding mothers. Data analysis included univariate and bivariate methods, using the Shapiro-Wilk normality test and the Wilcoxon test for bivariate analysis. The results show that out of 34 postpartum mothers surveyed, the chi-square test yielded a p-value of 0.000 (< 0.05) for diet and 0.018 (< 0.05) for chronic disease, indicating that both diet and chronic diseases influence sleep quality. Regarding effleurage massage, a p-value of 0.000 (< 0.05) was obtained, allowing the conclusion that Efflurage Massage has a significant effect on sleep quality. Therefore, there is an effect of efflurage massage on sleep quality in postpartum mothers at Bayu Asih Hospital, Purwakarta Regency in 2024.